Storage of cardenolides in Digitalis lanata cells. Effect of dimethyl sulfoxide (DMSO) on cardenolide uptake and release - Kreis, Wolfgang; Hoelz, Hubert; May, Ursula; Reinhard, Ernst (Plant Cell Tissue and Organ Culture, 1990)
Varius Digitalis lanata suspension cultures differing in their potential for biotransforming cardenolides were used to investigate the influence of dimethyl sulfoxide (DMSO) on cardenolide uptake, biotransformation and release. DMSO inhibited the accumulation of secondary glycosides (e.g. lanatoside A) but not of primary glycosides (e.g. β-methyldigitoxin). Cardenolide transformation was affected by DMSO both in vivo and in vitro resulting in almost complete inhibition at 20% DMSO (biotransformations in vivo) or 30 to 40% (enzyme activities in vitro). Further evidence has been obtained that cellular cardenolide accumulation during biotransformation of digitoxin involves the diffusion of secondary glycosides across the plasmalemma and the active uptake and vacuolar storage of primary glycosides. DMSO was used to permeabilize cultured Digitalis lanata cells. Only DMSO concentrations higher than 11% caused any release of cardenolides. The cells were, however, irreversibly damaged by this treatment. © 1990 Kluwer Academic Publishers.
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.storag
Keywords: cardiac glycosides; Digitalis lanata; dimethyl sulfoxide (DMSO); plant cell culture; storage; uptake